2012
DOI: 10.3389/fimmu.2012.00393
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer lytic-associated molecule plays a role in controlling tumor dissemination and metastasis

Abstract: Natural killer lytic-associated molecule (NKLAM) is an E3 ubiquitin ligase that plays a major role in the cytolytic activity of NK cells. NKLAM is rapidly synthesized and then targeted to the granule membranes of NK cells upon NK activation. Previous studies have shown an essential role for NKLAM in NK killing activity in vitro. These findings were extended to an in vivo model of NK-mediated tumor killing in which NKLAM-deficient knockout (KO) mice injected with B16 melanoma cells were found to have significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The use of EO771 cells in mouse models has the advantage of having tumor uptake close to 100%, in particular when an orthotopic mammary implantation is used 33 . This model is really close to human breast cancer (Figure 1).…”
Section: Eo771 Mammary Tumor Mouse Modelsmentioning
confidence: 96%
See 2 more Smart Citations
“…The use of EO771 cells in mouse models has the advantage of having tumor uptake close to 100%, in particular when an orthotopic mammary implantation is used 33 . This model is really close to human breast cancer (Figure 1).…”
Section: Eo771 Mammary Tumor Mouse Modelsmentioning
confidence: 96%
“…Despite their isolation in the late 1940s, characterization of hormonal receptors and classification of EO771 line remains controversial. Indeed, its classification diverges according to the authors, which is considered as triple negative in 10 publications 6,12,16‐23 and as ERα+ in 19 publications 13,24‐41 . Some authors prefer to mention the unclear status of this lineage 42,43 .…”
Section: Eo771 Cell Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Studies from our laboratory have demonstrated that NK cells from NKLAM-knock out (NKLAM-KO) mice have diminished anti-tumor activity [5]. Additionally, we have shown that NKLAM plays a role in controlling tumor metastasis [6]. As a family, RBR members have been shown to play a role in neurological diseases as well as innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells from NKLAM-deficient (KO) mice have diminished anti-tumor cytolytic activity (Hoover, et al, 2009). In vivo , NKLAM plays a role in controlling tumor metastasis (Hoover, et al, 2012). Recent studies from our laboratory have also demonstrated a role for NKLAM in macrophage bacterial killing.…”
Section: Introductionmentioning
confidence: 99%